BAGAIMANA PEMAHAMAN LITERASI SAINS PADA CALON GURU PENDIDIKAN ANAK USIA DINI (PIAUD) - Rahmawati, Jevi Milda; Suwarno, Suwarno (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2021)
The XXI century is an era for mastering several skills, one of which is scientific literacy. These skills need to be mastered by everyone in order to contribute to solving environmental problems. Existing research generally measures scientific literacy at the elementary, junior high, high school and higher education levels. These skills should be taught from an early age in children. Therefore, prospective Early Childhood Education teachers must understand these skills well. This type of research is a quantitative descriptive study with data collection techniques through a survey conducted on PIPIAUD STIT Muhammadiyah Tempurejo students who have taken PIAUD science courses. The survey results show that 58.3% of students do not understand science literacy skills. 66.7% of prospective PIAUD teacher students consider that science as a bridge to teach scientific literacy to early childhood is an abstract and difficult material to teach.